Impacts of two-phase nanofluid approach toward forced convection heat transfer within a 3D wavy horizontal channel - Alsabery, Ammar I.; Sidik, Nor Azwadi Che; Hashim, Ishak; Muhammad, Nura Muaz (Chinese journal of physics (Taipei), 2022)
Combined approach of geometrical variations to increase heat transfer surface with the application of high thermal conductive nanofluids can influence heat transfer enhancement in new thermal systems. This study numerically investigates the thermophoresis and Brownian diffusion as convective heat transfer enhancement mechanisms with two-phase Al2O3-water nanofluid in a 3D wavy horizontal channel having upper and lower wavy surfaces imposed with a uniform temperature and adiabatic conditions, respectively. Empirical correlations are used to model the thermal conductivity and viscosity as the most influential thermophysical properties of nanofluid. A commercial CFD code based on the Finite element Method (FEM) is employed to solve the governing equations in curvilinear coordinates for the computational domain. The employed dimensionless parameters include Reynolds number (Re), nanoparticle concentration (ϕ), channel’s number of oscillations (N) and amplitude (A). The current results correlate reasonably with similar experimental results in the literature. The results show that nanofluid flow in the wavy-channel augmented heat transfer, especially at increasing nanoparticle volume fraction and Reynolds number. Also, higher convective heat transfer is attained with increasing flow mixing due to increase in oscillation frequency. Local Nusselt number of nanofluid significantly rises when the Re varied from 200 to 1000 by about 75% at ϕ=0.02, N=4 and A=0.1. [Display omitted] •The impact of two-phase nanofluid approach on convection heat transfer in a 3D wavy horizontal channel is described.•Finite element method was used to solve the dimensionless governing equations subject to the selected boundary conditions.•Comparisons with the experimental/numerical data are accomplished regarding to the validity of the existing code.•The heat transfer rate increases with the raising of both wave amplitude and number of oscillations.